Association of erectile dysfunction and cardiovascular disease: an umbrella review of systematic reviews and meta‐analyses. (9th January 2021) - Mostafaei, Hadi; Mori, Keiichiro; Hajebrahimi, Sakineh; Abufaraj, Mohammad; Karakiewicz, Pierre I.; Shariat, Shahrokh F.
Abstract : Objectives: To present an overall picture of the evidence regarding the association of erectile dysfunction (ED) with cardiovascular disease (CVD). Methods: Systematic reviews and meta‐analyses that studied the association of ED with any CVD were included in this umbrella review. We did not restrict the population to a particular group or age. PubMed, Embase, the Joanna Briggs Institute (JBI) Database of Systematic Reviews and Implementation Reports, the Cochrane Database of Systematic Reviews, the Database of Abstracts of Reviews of Effects, and the PROSPERO register were searched to find relevant systematic reviews, with or without meta‐analyses, from inception to April 2020. The JBI Checklist for Systematic Reviews and Research Syntheses was used for the critical appraisal. Only studies with acceptable quality were included. Two independent reviewers extracted the data using the JBI data extraction tool for qualitative and quantitative data extraction. Results: The summary estimate showed a higher risk of CVD (relative risk [RR] 1.45, 95% confidence interval [CI] 1.36–1.54; P < 0.001), coronary heart disease (RR 1.50, 95% CI 1.37–1.64; P < 0.001), cardiovascular‐related mortality (RR 1.50, 95% CI 1.37–1.64; P < 0.001), all‐cause mortality (RR 1.25, 95% CI 1.18–1.32; P < 0.001), myocardial infarction (RR 1.55, 95% CI 1.33–1.80; P < 0.001) and stroke (RR 1.36, 95% CI 1.26–1.46; P < 0.001) in patients with ED than in other patients. Conclusions: Our results confirm that ED is an independent predictor of CVD and their outcomes. ED and CVD are two presentations of the same physiological phenomenon. ED normally precedes symptomatic CVD, providing a window of opportunity for healthcare practitioners to screen and detect high‐risk patients early to prevent avoidable morbidity and mortality.